The Identity Construction of Jordanian Muslim Woman Reflected in Willow Trees Don’t Weep Novel (2014) by Fadia Faqir - Ida Rosida; Molalita Molalita (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2016)
This article discusses the identity construction of a Jordanian Muslim woman through the main female character named Najwa reflected in Willow Trees Don’t Weep novel (2014) by Fadia Faqir. The method used in this study is descriptive qualitative. It is supported by the concept of identity by Stuart Hall and that of patriarchy to analyze the text. The aim of the study is to point out how Najwa, as a Jordanian Muslim woman who lives in a strong patriarchal culture without male figure in her family, constructs her identity, particularly when travelling to some different countries including Pakistan, Afghanistan, and England just to find her father. The way Najwa Lives in a new country, where she interacts with new people and be immersed in new culture, has an immense impact on her. Subsequently self-identity construction is definitely inevitable. Here, Najwa herself strives to negotiate and articulate her identity through her appearance and behavior, especially in Islamic practices and rituals. Consequently, the negotiation and articulation turn out to be the two major things in her self-identity construction. Culture, however, becomes a crucial mean to identity. Different culture represents different identity, and it keeps changing relaying on place where she lives.DOI: 10.15408/insaniyat.v1i1.4169